Attitudes and Perceived Information Technology Competency among Teachers - Sa'ari, Juanna Risah; Wong, Su Luan; Roslan, Samsilah (2005)
The purpose of this study was to measure teachers’ attitudes and perceived competency towards information technology (IT). The results revealed that most teachers possess positive attitudes towards IT. The findings also established that most teachers have moderate levels of IT competency. They also believe that they still lack the appropriate IT skills to integrate the technology into the teaching and learning process. The results of MANOVA analysis indicated that there are significant differences between the group of competent and incompetent teachers in terms of usefulness, confidence, anxiety and aversion toward the use of IT.